A Serious Game with Augmented Reality to Improve Cognitive Learning of Computer Networks - Dwi Ratnawati; Vivianti Vivianti; Yuwono Indro Hatmojo; Shoffan Saifullah (Institute of Multidisciplinary Research and Community Service, 2026)
Understanding computer networks requires a strong cognitive foundation, particularly in mastering abstract concepts such as network topology, device configuration, and data transmission processes. However, conventional learning methods are often limited in providing concrete visualization and interactive experiences. This study aims to develop and evaluate a serious game integrated with augmented reality (AR) technology to improve students’ cognitive learning outcomes in computer networks. This research employed a development approach by integrating serious game design with AR-based visualization. The development process involved asset creation, learning objective formulation, scenario design, and the implementation of problem-based cases on computer network concepts. The resulting product allows students to interact with virtual network devices in a real-world environment via mobile devices, enabling flexible learning anytime, anywhere. The evaluation phase included expert validation, user testing, and effectiveness testing. The results indicated that the developed media is feasible and effective for learning. Media expert validation reached 73.50%, while material expert validation achieved 87.50%, both categorized as highly feasible. User responses showed a feasibility level of 85.26%, indicating positive acceptance. Furthermore, the effectiveness test demonstrated a moderate improvement in students’ cognitive learning outcomes, with a gain percentage of 64.41%. The quantitative scores were obtained by converting Likert-scale ratings into percentages using a standardized formula to ensure transparency and consistency in data analysis. In conclusion, the integration of serious games and augmented reality provides an interactive and contextual learning experience that supports cognitive understanding of computer networks. This approach is considered both feasible and sufficiently effective for implementation in vocational education settings, particularly in technology-based learning environments. Keywords: Computer network learning, Serious game, Augmented reality, Learning media development, Effectiveness evaluation.